Artificial intelligence challenges in the face of biological threats: emerging catastrophic risks for public health - de Lima, Renan Chaves; Sinclair, Lucas; Megger, Ricardo; Maciel, Magno Alessandro Guedes; Vasconcelos, Pedro Fernando da Costa; Quaresma, Juarez Antônio Simões (Frontiers in Artificial Intelligence, 2024)
The threat landscape of biological hazards with the evolution of AI presents challenges. While AI promises innovative solutions, concerns arise about its misuse in the creation of biological weapons. The convergence of AI and genetic editing raises questions about biosecurity, potentially accelerating the development of dangerous pathogens. The mapping conducted highlights the critical intersection between AI and biological threats, underscoring emerging risks in the criminal manipulation of pathogens. Technological advancement in biology requires preventative and regulatory measures. Expert recommendations emphasize the need for solid regulations and responsibility of creators, demanding a proactive, ethical approach and governance to ensure global safety.